2016
DOI: 10.5858/arpa.2015-0454-oa
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Cell-Transfer Technique for Molecular Testing on Hematoxylin-Eosin–Stained Sections: A Viable Option for Small Biopsies That Lack Tumor Tissues in Paraffin Block

Abstract: Context.-In some instances the standard method of doing molecular testing from formalin-fixed, paraffinembedded block is not possible because of limited tissue. Tumor cell-enriched cell-transfer technique has been proven useful for performing immunocytochemistry and molecular testing on cytologic smears.Objective.-To establish the cell-transfer technique as a viable option for isolating tumor cells from hematoxylineosin (H&E)-stained slides.Design.-Molecular testing was performed by using the cell-transfer tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Cytology laboratories use a wide variety of collection media, fixatives, and stains for specimen preparation. A wide range of cytology specimen processing techniques were identified in the systematic review, including CytoLyt (Hologic Inc, Marlborough, Massachusetts), [141][142][143] Hanks, 44 RPMI, 144 saline, 111,132,[145][146][147][148][149][150][151][152][153][154][155] and CytoRich (Becton, Dickinson and Company, Franklin Lakes, New Jersey) 43 as collection media; alcohol, 6,46,115,156 formaldehyde, 112 Mount-Quick, 119 and formalin || as fixatives; and Diff-Quik, 6,44,46,166 Giemsa, 43 and Papanicolaou for staining. 46,167 However, none of the listed studies performed direct comparisons between the different processing techniques that enable making a specific recommendation for the use of one method over another.…”
Section: Additional Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cytology laboratories use a wide variety of collection media, fixatives, and stains for specimen preparation. A wide range of cytology specimen processing techniques were identified in the systematic review, including CytoLyt (Hologic Inc, Marlborough, Massachusetts), [141][142][143] Hanks, 44 RPMI, 144 saline, 111,132,[145][146][147][148][149][150][151][152][153][154][155] and CytoRich (Becton, Dickinson and Company, Franklin Lakes, New Jersey) 43 as collection media; alcohol, 6,46,115,156 formaldehyde, 112 Mount-Quick, 119 and formalin || as fixatives; and Diff-Quik, 6,44,46,166 Giemsa, 43 and Papanicolaou for staining. 46,167 However, none of the listed studies performed direct comparisons between the different processing techniques that enable making a specific recommendation for the use of one method over another.…”
Section: Additional Discussionmentioning
confidence: 99%
“…Although no study directly compared the use of one fixative with another, 4 studies 70,91,119,120 reporting on adequacy for ancillary testing or successful ancillary testing following fixation with 10% neutral buffered formalin comprise the indirect evidence supporting this statement. Studies reporting on mutational analysis comprise 2 prospective cohort studies, 70,119 and 2 retrospective cohort studies. 91,120 One of the prospective cohort studies 70 also reported on IHC and FISH, and 1 retrospective cohort study 91 reported on FISH in addition to mutational analysis.…”
Section: Considerations For Ancillary Studies During Malignant Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular testing performed on H&E-stained sections via CTT has also been utilized when tissue from cell blocks and small surgical biopsy samples were exhausted and the only available material for testing was present on the H&E-stained slides. Wu et al [36] applied PCR-based molecular testing (EGFR, BRAF, KRAS) using CTT on 97 samples, with 85% success rate, no significant residual tissue in the paraffin block for ancillary testing, with similar success.…”
Section: Cell Transfer Techniquementioning
confidence: 99%